2013
DOI: 10.1111/bdi.12137
|View full text |Cite
|
Sign up to set email alerts
|

Public health significance of bipolar disorder: implications for early intervention and prevention

Abstract: Considering the major impact of BD on patients and society, there is an urgent need for the development of early intervention strategies aimed at earlier detection and more specific treatment of the early phase of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 83 publications
2
50
0
2
Order By: Relevance
“…Relative to people with normal weight, all‐cause mortality of obese persons is higher . We surmise that the increased prevalence of obesity in individuals with SCZ and BP puts them at greater health and mortality risk than the population at large, consistent with previous observations . The trajectory of weight gain is also important.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Relative to people with normal weight, all‐cause mortality of obese persons is higher . We surmise that the increased prevalence of obesity in individuals with SCZ and BP puts them at greater health and mortality risk than the population at large, consistent with previous observations . The trajectory of weight gain is also important.…”
Section: Discussionsupporting
confidence: 88%
“…37 We surmise that the increased prevalence of obesity in individuals with SCZ and BP puts them at greater health and mortality risk than the population at large, consistent with previous observations. 8,9,11,[19][20][21] The trajectory of weight gain is also important. Obese persons with upward weight gain trajectories, even after controlling for demographic and socioeconomic characteristics, smoking status, limitations in activities of daily living, and a wide range of chronic illnesses, have even higher mortality risk than those with static obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The possibility of pluripotential (shared) early stages across different disorders has been proposed based on a degree of overlap in nonspecific early risk syndromes. 7,30,35 However, this proposal is problematic in many ways. It ignores the welldocumented and striking differences in developmental history, early illness trajectories, and family history between prototypical schizophrenia and classical recurrent BD.…”
Section: 26mentioning
confidence: 99%
“…Linkage studies have revealed that SCZ and bipolar disorder share a number of overlapping features and genetic risk variants . Bipolar disorder is associated with neurocognitive deficits that persist into euthymia after episode resolution . Several meta‐analyses have revealed impairments in the broad domains of attention, processing speed, verbal memory and executive functions, with relative preservation of verbal abilities and intelligence.…”
Section: Introductionmentioning
confidence: 99%